Changing trends in lung cancer disease burden between China and Australia from 1990 to 2019 and its predictions - Dan Zhao; Haijun Mu; Ping Yu; Chao Deng (Thoracic Cancer)
Abstract Purpose Lung cancer (LC) is a leading cause of death and presents a substantial societal burden. This article compares its disease burden and risk factors between China and Australia to support health policymakers for LC prevention and treatment. Materials and Methods The data from the 2019 Global Burden of Disease Study were used to analyze disease temporal trends using Joinpoint regression model. The Bayesian age‐period‐cohort model was used for prediction. The population‐attributable fraction (PAF) was used to analyze LC risk factors. Results In 2019, the age‐standardized rates (ASR) of incidence and of mortality of LC in China were 41.71/100 000 and 38.70/100 000, while Australia's rates were 30.45/100 000 and 23.46/100 000. It showed an increasing trend in China but a decreasing trend in Australia. By 2030, the ASR of incidence and mortality are predicted to be 47.21/100 000 and 41.54/100 000 in China, while Australia's rates will reach 30.09/100 000 and 23.3/100 000, respectively. Smoking is the most common risk factor for LC, followed by particulate matter and occupational carcinogenesis. The PAF of smoking dropped in Australia (from 68.38% to 53.75% in females; 77.41% to 58.47% in males) but increased in China (from 19.56% to 26.58% in females; 80.45% to 82.03% in males) from 1990 to 2019. Conclusions The disease burden of LC in China is rising, whereas in Australia, it is declining. China still faces a heavy LC burden. Risk factor analysis supported for further improving the compliance and enforcement of polices on tobacco control and environmental management to reduce this disease burden.